Hydrological response of semi-arid river catchment to rainfall and temperature fluctuations - Umar, Da'u Abba; Ramli, Mohammad Firuz; Aris, Ahmad Zaharin; Zaudi, Muhammad Amar (Universiti Putra Malaysia Press, 2019)
Determining the response of basin water resources to rainfall and temperature fluctuations is a crucial source of information for basins water resources planning and management. The study used a descriptive, Mann-Kendall trend test (M-K) and Multiple Linear Regression (MLR). The mean, standard deviations and variations were spatially interpolated using the geostatistical technique. The trend results showed an increase in both rainfall and temperature series. However, the only statistically significant trends were in June and September for rainfall series and in February, May, and April for the temperature series. Rainfall exhibited high temporal variability whereas temperature showed high spatial variability. The intra-annual variability was higher than the inter-annual variability, suggesting that the local climate is largely controlled by natural force. The result of the multiple linear regression (R2=0.431), indicates that the hydrology and water resources of the basin are impacted largely by factors not considered in this study such as land use changes, infiltration, and rate of evaporation among others. However, among the factor considered, rainfall (Beta = 0.505; P = 001) has the highest impacts on the river discharge behavior and should be given preference while addressing water resources predicaments in the catchment.